Impact of family capital & social capital on youth entrepreneurship – a study of Uttarakhand state, India - Lalit Sharma (Journal of Global Entrepreneurship Research, 2014)
The research paper intends to interpret how the three forms of family capital viz. family's financial capital, family's man power capital and family's human capital influences the career choice intention of students of HEI's of Uttarakhand, India. Additionally the study also evaluates the impact of student's individual social capital on his career intent. This is a quantitative study conducted at Uttarakhand state of India on a large sample of students studying in various professional courses of Uttarakhand. The research validates a positive relationship between the family's financial capital and higher education intention of students. The study found no influence of family's financial capital (measured as father's annual income), manpower capital (measured as family size) and human capital (measured as father's occupation) on career intentions of students. The study confirmed that there is a significant impact of students' social capital network span on his career intentions, especially in taking up entrepreneurship as a career choice.
Keywords: D20; G34; L10; 650; Entrepreneurship; Factors influencing career choices; Family impact oncareer; Youth entrepreneurship in Uttarakhand; Family and career intentions; Familycapital & youth entrepreneurship; Social capital & youth entrepreneurship